2004
DOI: 10.3748/wjg.v10.i14.2147
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microvessel density and telomerase activity in hepatocellular carcinoma

Abstract: MVD and telomerase activity may serve as diagnostic criteria of HCC in earlier stage. Meanwhile, there may be a cooperative effect between MVD and telomerase on the growth and metastasis of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
5
2
1
Order By: Relevance
“…MVC was not associated with any clinicopathological factors or recurrence rate after hepatectomy in either the present study or our pilot study [17] . In contrast to our results, El-Assal et al [30] and other investigators [6,14,15,[30][31][32] have reported that microvessel density in HCC is increased in larger tumors, tumors with poor differentiation and cirrhotic patients, while higher microvessel density is associated with intra-hepatic recurrence. In the present study, however, MVC did not correlate with co-existing cirrhosis or with various etiological factors related to chronic hepatitis such as viral status.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…MVC was not associated with any clinicopathological factors or recurrence rate after hepatectomy in either the present study or our pilot study [17] . In contrast to our results, El-Assal et al [30] and other investigators [6,14,15,[30][31][32] have reported that microvessel density in HCC is increased in larger tumors, tumors with poor differentiation and cirrhotic patients, while higher microvessel density is associated with intra-hepatic recurrence. In the present study, however, MVC did not correlate with co-existing cirrhosis or with various etiological factors related to chronic hepatitis such as viral status.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of MVC for tumor relapse or progression might not be particularly strong. This result contradicts findings in other reports described above [6,14,16,30,31] . As explained above, HCC naturally acquires rich tumor vascularity in the early stages and most clinically treated HCCs represent tumor with radiological enhancement [34,35,38] .…”
Section: Overall Survival Rate (%)contrasting
confidence: 88%
See 1 more Smart Citation
“…We found that there was no difference in intratumoural TMA levels detected at different time points of tumour growth suggesting that TMA levels in tumour tissue are independent of tumour size. This is similar to the results of Piao et al, 18 who found no correlation with TMA activity and tumour size. However, we found that TMA in the peritumoural tissue increased with time, along with the growth of the implanted tumour.…”
Section: Discussionsupporting
confidence: 82%
“…19 On the other hand, another report showed that telomerase activation was signi cantly related to the poor tumor differentiation of HCC tumors. 24 In thyroid cancer, TERT promoter mutation was frequently observed in poorly differentiated tumors. 25 The role of TERT is not only the acquisition of tumor immortality, but also interactions with several oncogenic pathways such as the Wnt/beta-catenin signal pathway and p53 suppression.…”
Section: Discussionmentioning
confidence: 99%